Effect of the Use of Different Acoustic Stimuli on Cortical Auditory Evoked Potentials and Autonomic Cardiac Modulation - Fiuza Regaçone, Simone [UNESP]; Valenti, Vitor Engrácia [UNESP]; Figueiredo Frizzo, Ana Cláudia [UNESP] (Wiley, 2018)
Purpose. The aim of this study was to analyze the relationship between Cortical Auditory Evoked Potentials (CAEPs) measurements and autonomic cardiac modulation in relation to different acoustic stimuli and to verify which of these stimuli have more influence on the autonomic nervous system. Methods. Sixty healthy women, aged between 18 and 25 years, participated in this study. Prior to the CAEP examination, blood pressure and resting heart rate were measured using a stethoscope, sphygmomanometer, and the Polar RS800CX cardiofrequency measures. After the collection of these measures, the CAEP test was started simultaneously with the HRV collection. Results. All the HRV indices presented correlations with the components of the CAEPs. During the acoustic stimulation, a predominance of the modulation of the autonomic parasympathetic nervous system was observed. The harmonic and disharmonic stimuli were the ones that presented the most correlations between the measures analyzed in this study. Conclusions. There was an association between CAEP and cardiac autonomic modulation in relation to different acoustic stimuli. Among the acoustic stimuli used in this study, the ones that most influenced the autonomic cardiac modulation were harmonic and disharmonic stimuli, which are acoustically more complex stimuli.